From Cooperation to Confrontation: The Dynamics of the Buton Sultanante – VOC Relations from Sultan Dayanu Ikhsanuddin to Sultan Himayatuddin Muhammad Saidi (1613–1763) - Muliadin Iwan; Dewi Susilawati; Abrar Abrar (Jurnal Pendidikan Sejarah, 2026)
This article examines the dynamics of the relationship between the Sultanate of Buton and the Dutch East Indies Company (VOC, the Vereenigde Oostindische Compagnie), which experienced fluctuations from the reigned of Sultan Dayanu Ikhsanuddin or La Elangi (1578–1615) to the reigned of Sultan Himayatuddin Muhammad Saidi or La Karambau (1751–1752 and 1760–1763). applying the historical research method, this article reconstructs past events in a systematic, critical, and objective manner based on authentic and relevant historical sources through four main stages: heuristics, source criticism, interpretation, and historiography. The findings show that the relationship between Buton and the VOC was initially built on shared interests through various alliance treaties that were continuously renewed. Both parties were mutually dependent: Buton needed VOC protection from threats posed by surrounding kingdoms, while the VOC required Buton as a safe stopover point on its route to the Spice Islands of Maluku. However, over time, the relationship did not always run smoothly. Differences in political and economic interests, foreign intervention, and the failure of both parties to fulfill the terms of their agreements caused the relationship to fluctuate. At different times, they acted as allies cooperating with each other, while at other times they became adversaries in conflict.